Ultrasonographic Finding of Gastric Carcinoma Patients in a Teaching Hospital of Bangladesh - Kabir, AKM Golam; Nahar, Mst Nazmun; Noor-E-Alam, Sheikh Mohammad; Kabiruzzaman, Mohammad; Hossain, Ahmed; Ara, Showkat (Journal of Current and Advance Medical Research, 2018)
Background: Ultrasonographic findings of gastric carcinoma are varied in different population in different region. Objectives: The purpose of the present study was to see the different ultrasonographic findings of stomach cancer patients attended at a tertiary care hospital in Dhaka city. Methodology: This cross-sectional study was carried in the department of Radiology and Imaging of Dhaka Medical College, Dhaka during July 2009 to June 2011for a period of 2(two) years. Clinically suspected gastric carcinoma patients were evaluated by ultrasonography of upper abdomen and or Barium-meal x-ray evaluation. The sonographic findings were noted. Biopsy was performed by endoscopy or by surgical resection to confirm the case. Result: A total number of 60 gastric carcinoma patients were recruited.In all 24 patients of gastric carcinoma (100%) wall layering was completely lost. Wall thickness was increased in all the 24 cases (100%). Patients with gastric carcinoma had a wall thickness ranging from 10mm to 38mm with an average wall thickness of 24.5 mm. There was luminal narrowing and reduced peristalsis seen in all the 24 cases. Heterogeneous intraluminal masses were seen in 20 out of 24 (83.33%) cases of gastric carcinoma. Serosal involvement was seen in 17 out of 23 (70.83%) cases. Conclusion: Ultrasonography of gastric carcinoma shows completely lost of wall layering of stomach with increased thickness of it. Journal of Current and Advance Medical Research 2016;3(2):51-55